2018
DOI: 10.5489/cuaj.5610
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on Competence by Design in urology

Abstract: Introduction: The Royal College of Physicians and Surgeons of Canada has begun implementing Competence by Design (CBD). However, it is unclear how much urology trainees and faculty know about CBD, their attitudes towards this change, and their willingness to embrace and participate in this new model of training.Methods: This cross-sectional study was conducted through an online survey, which was administered to all trainees and faculty at Canadian urology programs prior to the implementation of CBD. The final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This is consistent with other studies from anesthesiology and urology residency training programs in which evaluation fatigue and greater resource intensity have been identified as significant concerns associated with CBME. 10 , 12 , 14 , 15 Our findings highlight an inherent tension between faculty members’ desire to provide meaningful, timely feedback and a perceived lack of time to do so. Indeed, previous evidence suggests that faculty are currently underprepared for their role in workplace-based assessment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is consistent with other studies from anesthesiology and urology residency training programs in which evaluation fatigue and greater resource intensity have been identified as significant concerns associated with CBME. 10 , 12 , 14 , 15 Our findings highlight an inherent tension between faculty members’ desire to provide meaningful, timely feedback and a perceived lack of time to do so. Indeed, previous evidence suggests that faculty are currently underprepared for their role in workplace-based assessment.…”
Section: Discussionmentioning
confidence: 86%
“…1,[6][7][8][9] As faculty and learners alike are introduced to the CBD framework, implementation of an educational paradigm without first assessing program readiness is a potential impediment to successful implementation. 10,11 In the 2018 Resident Doctors of Canada (RDoC) national survey of residents, 30.2% of respondents indicated that their programs had rolled out CBME and 17.0% of respondents indicated that they were formally participating in this training model. 12 Of those residents in training programs which had rolled out the CBME model, 64.4% of residents reported that they felt adequately informed about CBME and 36.5% of respondents felt that their preceptors were adequately informed about CBME; however, it is noted that this survey did not provide preceptors' perceptions of their preparedness for CBD.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,13 An increase in personalized and regular feedback has been identified as one of the top perceived benefits of CBD by both residents and supervisors in Canadian urology training programs. 14 However, although residents in a CBD-based internal medicine program valued the idea of feedback, in practice constant feedback seeking was burdensome. 15 The quantity of feedback had increased, but the quality had decreased and constant assessments interrupted daily compare and discuss meaning, codes and initial themes.…”
Section: Introductionmentioning
confidence: 99%
“…The Fellowship Council (FC) is an association of program directors and specialty societies that accredits fellowship training programs to ensure uniformity and to maintain a standard of excellence for fellowship trained surgeons. Beginning in 2015, the Fellowship Council (FC) began a transformation to a CBME framework [ 6 9 ]. In this approach, a set of EPAs (Entrustable Professional Activities) are defined and provide a practical and intuitive way to assess competency based on the level of supervision [ 10 , 11 ].…”
mentioning
confidence: 99%
“…However, the move to a competency-based model is a true culture shift in surgery. Challenges in implementation may include lack of faculty and trainee “buy-in”, inability to find the time to submit EPAs, lack of training and simply forgetting to complete the assessments due to an already busy workflow [ 6 9 ]. Fellowship-level EPA assessment is also different from residency-level EPA.…”
mentioning
confidence: 99%